IMPLEMENTASI ALAT PERMAINAN EDUKATIF DALAM MENGEMBANGKAN KETERAMPILAN SOSIAL PADA ANAK USIA DINI PAUD KEMAS NUSA INDAH KECAMATAN BAROS - Rachmatullah Jundi (LPPM Universitas Bina Bangsa, 2024)
This research aims not only to validate the researchers' assumptions, but rather the aim of the research, namely: to find out how to use creative educational game media in training the social skills of PAUD children in Kemas Nusa Indah, Baros District. so as to be able to make early childhood education active in directing students to be able to actualize learning within themselves and the environment in which they find themselves. The research model was carried out based on data preparation according to Miles and Huberman, the stages followed were data reduction, data display and conclusions. The data collection techniques are carried out using observation, interviews and documentation. in training the social skills of PAUD children in Kemas Nusa Indah, Baros District, due to the lack of professional staff, children still have to adapt to social game activities, they still need training in developing creative game media that can stimulate children's social skills, explore personal competence, social competence. and pedagogical competence as well as conducting outreach or training in order to develop a variety of game media that can stimulate the development of children's social skills